A Phase 1 Study of CUDC-101, a multitarget inhibitor of HDACs, EGFR, and HER2, in combination with chemoradiation in patients with head and neck squamous cell carcinoma - Galloway, Thomas (Clin Cancer Res, 2015)
PURPOSE: CUDC-101 is a small molecule that simultaneously inhibits the epidermal growth factor receptor (EGFR), human growth factor receptor 2 (HER2), and histone deacetylase (HDAC) with preclinical activity in head and neck squamous cell cancer (HNSCC). The primary objective of this investigation is to determine the maximum tolerated dose (MTD) of CUDC-101 with cisplatin-radiation in the treatment of HNSCC. EXPERIMENTAL DESIGN: CUDC-101 monotherapy was administered intravenously thrice weekly (M/W/F) for a 1-week run-in, then continued with concurrent cisplatin (100 mg/m(2) every 3 weeks) and external beam radiation (70 Gy to gross disease) over 7 weeks. RESULTS: Twelve patients with intermediate or high risk HNSCC enrolled. Eleven were p16INKa (p16) negative. The MTD of CUDC-101 based combination therapy was established at 275 mg/m(2)/dose. Five patients discontinued CUDC-101 due to an adverse event (AE); only one was considered a dose limiting toxicity (DLT), at the MTD. Pharmacokinetic evaluation suggested low accumulation with this dosing regimen. HDAC inhibition was demonstrated by pharmacodynamic analyses in peripheral blood mononuclear cells (PBMCs), tumor biopsies, and paired skin biopsies. Paired tumor biopsies demonstrated a trend of EGFR inhibition. At 1.5 years of median follow-up, there has been one recurrence and two patient deaths (neither attributed to CUDC-101). The remaining 9 patients are free of progression. CONCLUSIONS: CUDC-101, cisplatin and radiation was feasible in intermediate/high risk patients with HNSCC, with no unexpected patterns of AE. Although the MTD was identified, a high rate of DLT-independent discontinuation of CUDC-101 suggests a need for alternate schedules or routes of administration.